2016
DOI: 10.1016/j.compstruct.2016.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of the FRP-to-concrete interface subject to moisture ingress: Effects of conditioning methods and silane treatment

Abstract: Please cite this article as: Amidi, S., Wang, J., Deterioration of the FRP-to-concrete interface subject to moisture ingress: effects of conditioning methods and silane treatment, Composite Structures (2016), doi: http://dx. AbstractFiber reinforced plastics (FRP) composites have emerged as one popular material in retrofit/rehabilitation of concrete structural members in last decades. The long-term durability of the FRP-to-concrete interface in aggressive environments plays a critical role in the success of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Generally, plasticization, swelling, hydrolysis and differential stress may develop owing to moisture uptake [95,96]. Swelling of a polymer is proportional to its moisture content and increases with increasing relative humidity [97]. The swelling of a polymer matrix and the plasticization of its structure may be recovered after drying; the recovery depends on the constituents and quality of adhesives.…”
Section: Moisture Conditionsmentioning
confidence: 99%
“…Generally, plasticization, swelling, hydrolysis and differential stress may develop owing to moisture uptake [95,96]. Swelling of a polymer is proportional to its moisture content and increases with increasing relative humidity [97]. The swelling of a polymer matrix and the plasticization of its structure may be recovered after drying; the recovery depends on the constituents and quality of adhesives.…”
Section: Moisture Conditionsmentioning
confidence: 99%
“…Use of saline coupling agents to improve the interfacial bond behavior between FRP and concrete has proved effective both under normal conditions 219,220 and under hygrothermal exposure. 221,222 Due to its ability to induce covalent bonds between the epoxy and concrete, a much stronger adhesion than the hydrogen bond between the epoxy and concrete results. 221 This helps in achieving a more durable FRP–concrete bond under water attack.…”
Section: Implemented Approaches For Improving the Frp–concrete Bond Pmentioning
confidence: 99%
“…In addition to the use of saline treatment to improve the FRP–concrete bond, it has been shown that the use of a new conditioning method by partial submergence of only the bottom half (containing the FRP–concrete bond interface) of the test specimen is more effective in improving the fracture toughness than the case with full submergence of the specimens. 222…”
Section: Implemented Approaches For Improving the Frp–concrete Bond Pmentioning
confidence: 99%
“…moisture penetration, temperature change, chloride ion penetration, and alkalinity in its service life. Among these environmental effects, the moisture penetration is reported as one of the most critical factors which significantly reduces the load bearing capacity of the reinforced element from its designed value and causes unexpected failure of structures [1][2][3][4][5][6][7][8][9]. Under the moisture condition, deterioration of the mechanical property of composite system could be caused by the strength reduction of the FRP composites, plasticization of the polymer matrix or the degradation of interface between adhesion and substrate [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%